2021
DOI: 10.3390/en14164998
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment on Different Synthetic Routes of ZIF-8 Nanomaterials

Abstract: In the last twenty years, research activity around the environmental applications of metal–organic frameworks has bloomed due to their CO2 capture ability, tunable properties, porosity, and well-defined crystalline structure. Thus, hundreds of MOFs have been developed. However, the impact of their production on the environment has not been investigated as thoroughly as their potential applications. In this work, the environmental performance of various synthetic routes of MOF nanoparticles, in particular ZIF-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…3 In addition, the present study completes some of the recent attempts ( e.g. recycling solvents and reagents from the synthesis or spent mother liquors 12–17 in line with the high environmental impact of organic solvents in the MOF synthesis 18 ) to make the synthesis of MOFs more sustainable, none of them dealing with the dissolution of the MOF to purify and reuse its ligand. The reuse of this ligand from discarded ZIF-94/SIM-1 crystals would save an important part of the energy and resources needed to produce new ligand.…”
supporting
confidence: 60%
“…3 In addition, the present study completes some of the recent attempts ( e.g. recycling solvents and reagents from the synthesis or spent mother liquors 12–17 in line with the high environmental impact of organic solvents in the MOF synthesis 18 ) to make the synthesis of MOFs more sustainable, none of them dealing with the dissolution of the MOF to purify and reuse its ligand. The reuse of this ligand from discarded ZIF-94/SIM-1 crystals would save an important part of the energy and resources needed to produce new ligand.…”
supporting
confidence: 60%
“…They found that the solvents used in the cleaning and purification steps of MOF synthesis had an equal or greater impact on the environmental index, which should avoid the use or perform the reutilization of the solvent. Ntouros et al 130 adopted the LCA to investigate and evaluate the five synthetic routes for the production of ZIF-8 and found that deionized water as a solvent was more environmentally friendly than DMF and methanol. Hughes et al 131 investigated “basic” (no bed cooling during adsorption) and “modified” (bed cooling during adsorption) temperature swing adsorption (TSA) processes using dmpn-Mg 2 (dobpdc), respectively, and compared their process economics to the most advanced MEA capture systems.…”
Section: Application Of Mofs For Co2 Capturementioning
confidence: 99%
“…82−85 Ntouros et al explored five synthetic routes toward ZIF-8 nanomaterials. 82 They showed that the use of methanol as a solvent accounts for 35% of the mean environmental impact, while this metric increases to 58% using DMF as a solvent. The use of deionized water as a solvent resulted in only 2% of the mean environmental impact, showing the negative impact of nonaqueous solvents.…”
Section: ■ Raw Materialsmentioning
confidence: 99%
“…We can look to the literature for LCA analyses of synthetic methods of other materials. Ntouros et al explored five synthetic routes toward ZIF-8 nanomaterials . They showed that the use of methanol as a solvent accounts for 35% of the mean environmental impact, while this metric increases to 58% using DMF as a solvent.…”
Section: Biaobxc Materials Productionmentioning
confidence: 99%